Education and State Formation - Green, Andy. author. aut Link
XII, 353 p.
Keywords: Britain was the last major European state to create a national education system and is set to be the first to dismantle it. In this wide-ranging comparative study, Andy Green examines the reasons for the uneven development of public education in England, Prussia, France and the USA.